Perceived Outcome and Knowledge of Quality Antenatal Care Among Nursing Mothers Attending Olabisi Onabanjo University Teaching Hospital, Sagamu, Ogun State, Nigeria. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Objective: This study aimed to assess the perceived outcome and knowledge of quality antenatal care among nursing mothers attending Olabisi Onabanjo University Teaching Hospital (OOUTH) in Sagamu, Ogun State, Nigeria.Methods: A descriptive cross-sectional study was used, data was collected  among 159 nursing mothers attending the antenatal care unit at OOUTH. Data were collected using a structured questionnaire that assessed the participants' demographic characteristics, perceived outcome of antenatal care, and knowledge of quality antenatal care. Data analysis was performed using descriptive statistics and inferential statistics.Results: The findings revealed that the majority of the nursing mothers had a positive perception of the outcomes of antenatal care, with 82% reporting satisfaction with the care received. However, there were gaps in their knowledge of quality antenatal care. Only 54% of the participants demonstrated good knowledge regarding essential antenatal care practices, such as regular blood pressure monitoring, iron and folic acid supplementation, and the importance of antenatal visits.Conclusion: The study highlighted the importance of perceived outcome and knowledge of quality antenatal care among nursing mothers attending OOUTH. Although the participants generally had a positive perception of the outcomes, there is no association between the perceived outcome of antenatal care and the number of pregnancies. This suggests a need for targeted educational interventions and improved communication between healthcare providers and nursing mothers to enhance their knowledge, perception, and promote optimal antenatal care utilization.